Resource provisioning in a multi-service enabled ADSL system - Xiaoning He; Hao Che (10th International Conference on Telecommunications : ICT'2003 : February 23-March 1, 2003, Sofitel Coralia Maeva Beach Hotel, Tahiti, Papeete, French Polynesia, 2003)
The resource provisioning issue for the discrete multi-tone (DMT) based asymmetric digital subscriber loop (ADSL) network is addressed. Currently, the provisioning scheme for ADSL network provisions the network based on the physical layer performance. However, provision for the network at the physical layer cannot provide assurance to TCP/UDP quality. The simulation results from previous work showed that there is a threshold for the bit-error rate (BER) above which TCP (transport control protocol) throughput drops quickly. A new idea of provisioning the resource based on the TCP/UDP performance is proposed. Based on the joint optimization scheme of bit loading rate at the physical layer and the TCP throughput performance at the transport layer , the architecture provides quality of service (QoS) guarantee for voice traffic and throughput assurance for TCP applications. Moreover, the architecture provides systematic procedures to allow an Internet service provider to establish service level agreement (SLA) with the customers. A case study is presented to demonstrate how the provisioning scheme works.